2020
DOI: 10.1002/ece3.6839
|View full text |Cite
|
Sign up to set email alerts
|

Caught in the Act: Variation in plastid genome inverted repeat expansion within and between populations of Medicago minima

Abstract: A plastid genome (plastome) containing large and small single-copy regions (LSC and SSC, respectively) separated by a large inverted repeat (IR) is widely acknowledged to represent the ancestral form of the plastome monomer of land plants. The typical plastome IR is on the order of 25-30 kb with most size variation driven by expansion and contraction of IR boundaries (Jansen & Ruhlman, 2012; Ruhlman & Jansen, 2014). The ancestral form is not, however, ubiquitous among photosynthetic plants. In disparate lineag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 47 publications
1
15
0
Order By: Relevance
“…1 b) showed even distribution of reads over the assembled plastome sequence when both copies of the IR are included and ~ two-fold higher depth of coverage over the IR region compared with SC regions when only one IR copy is considered. This adds another evidence to the IR reemergence in the IRLC in addition to previous findings in M. minima [ 11 , 31 ]. The IR reemergence in Melilotus dentata was further confirmed by multiple individuals, but with some INDELs (insertions and deletions) between the two IR copies in Melilotus dentata 02 and Melilotus dentata 03 (Fig.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…1 b) showed even distribution of reads over the assembled plastome sequence when both copies of the IR are included and ~ two-fold higher depth of coverage over the IR region compared with SC regions when only one IR copy is considered. This adds another evidence to the IR reemergence in the IRLC in addition to previous findings in M. minima [ 11 , 31 ]. The IR reemergence in Melilotus dentata was further confirmed by multiple individuals, but with some INDELs (insertions and deletions) between the two IR copies in Melilotus dentata 02 and Melilotus dentata 03 (Fig.…”
Section: Resultssupporting
confidence: 82%
“…A direct link between recombination and mutation hotspots was reported from the IR-lacking plastome of Lathyrus , in which c. 1.5 kb localized hypermutation region around ycf4 was caused by repeated DNA breakage and repair [ 20 ]. In addition, repeat-mediated recombination-dependent replication has caused a ~ 9 kb IR reemergence in Medicago minima [ 11 , 31 ]. Notably, plastomes of the IRLC species have abundant repetitive DNA and this seems to be rare in angiosperms’ chloroplast DNA (cpDNA) [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from concerns as to whether it is reasonable to recognize the plastome as a single locus ( Gonçalves et al, 2020 ; Doyle, 2021 ), one of the main and practical criticisms about whole plastome alignment without further filtration is that most gaps are located in AT-rich and low complexity regions, which are prone to high-level length polymorphisms in simple sequence repeats and falsely aligned non-orthologous sequences ( Duvall et al, 2020 ). The much longer whole plastome alignment of 244 legumes (313,335 bp) compared to the alignment lacking indels (64,099 bp) is not surprising when considering the dynamic gene, intron, intergenic, and repeat content across papilionoids (e.g., Milligan et al, 1989 ; Doyle et al, 1995 ; Bailey et al, 1997 ; Cai et al, 2008 ; Jansen et al, 2008 ; Sabir et al, 2014 ; Sveinsson and Cronk, 2014 ; Schwarz et al, 2015 ; Choi et al, 2019 , 2020a ; Jin et al, 2019 ; Oyebanji et al, 2020 ; Lee et al, 2021 ). The WP alignment extended well beyond the length of a typical plastome to accommodate for poorly aligned sequences.…”
Section: Discussionmentioning
confidence: 99%
“…Repeated sequences and rearrangements pose challenges to plastome assembly, and the choice of reference in reference-guided assembly or de novo assembly using sets of reads that map to references may bias against the detection of novel rearrangements. Plastome rearrangements are also not necessarily fixed within single taxa ( Gurdon and Maliga 2014 ; Choi et al 2020 ) and may not be fixed within single individuals sampled ( Guo et al 2014 ). Other forms of heteroplasmy, though not considered in this study, have been observed in an Astragalus plastome ( Lei et al 2016 ) as well.…”
Section: Discussionmentioning
confidence: 99%